Health worker perspectives on, and health system-level facilitators and barriers to early infant male circumcision for HIV prevention in a traditionally non-circumcising community, Northeastern Uganda: a cross-sectional qualitative study - Michael Ediau; Stephanie Brodine; Kimberly C. Brouwer; Anita Raj; Eyal Oren; Susan M. Kiene (BMC Health Services Research)
Abstract Background Voluntary medical male circumcision (VMMC) remains one of the recommended HIV prevention measures in heterosexual men in selected countries, including Uganda. While most VMMCs are on adolescent and adult males, its longer-term potential population-level impact might be realized through the inclusion of early infant male circumcision (EIMC). However, EIMC’s successful rollout requires understanding the perspectives of health workers, health system-level facilitators, and barriers to EIMC. Following EIMC pilot/project implementation, we explored health workers’ individual-level perspectives on, and health system-level facilitators and barriers (to EIMC) in a traditionally non-circumcising setting in Northeastern Uganda. Methods In April 2022, we conducted a qualitative study involving 26 in-depth interviews. Participants included seven health workers who participated in EIMC and seven who did not, two heads of hospitals that conducted EIMC, and six District health officials, four representatives of national-level partners who supported EIMC implementation in the study area. Data were coded and analyzed using inductive (for individual-level perspectives) and deductive (for health system-level barriers and facilitators) thematic analyses. Results Health workers who had participated in EIMC reported its comparative advantages, including performance simplicity, faster wound healing, and relatively lower cost. Some health workers who had not participated in EIMC expressed concerns regarding the safety of the procedure and the potential associated pain. Health system-related facilitators for EIMC included leadership support and availability of funding and supplies for initial implementation and health workers’ capacity building through EIMC training. This support was limited to the project’s period and later ended. Therefore, barriers to EIMC implementation, including a lack of supplies and funding, were reported. Conclusion EIMC was perceived as a comparatively beneficial intervention for possible HIV prevention because, compared to VMMC, it is technically simpler, safer, potentially low-cost, and wound healing is faster. Nevertheless, some health workers raised concerns about EIMC. Leadership support, funding, health workers’ EIMC training, equipment, and supplies availability facilitated EIMC. Some facilitators were short-lived as a lack of continued funding and supplies stock-outs were major EIMC barriers. Successful implementation requires sustained EIMC financing and addressing the concerns of some health workers, in addition to the identified health system-related barriers.